STRUKTUR ANATOMI DAN KERAPATAN SEL SEKRESI SERTA AKTIVITAS ANTIOKSIDAN EKSTRAK ETANOL DARI RIMPANG TEMULAWAK (Curcuma xanthorrhiza Roxb) ASAL KECAMATAN PENGARON KABUPATEN BANJAR KALIMANTAN SELATAN - Evi Mintowati Kuntorini; Maria Dewi Astuti; Norma Milina (Bioscientiae, 2011)
This study aimed to observe the anatomical structure and density of secretory cells as well as knowing activity of ethanol extract aktioksidan associated with cell density of the rhizome of Curcuma xanthorrhiza secretion originating from Sub Pengaron Banjar regency, South Kalimantan. Making preparations rhizome anatomy carried out by using Free Hand Section, the analysis of antioxidant activity using DPPH (1,1-diphenyl-2-pikrilhidrazil). Observations consisting of rhizome anatomical structure of cells of the epidermis, the cortex, endodermis and the central cylinder. In epidermal cells contained little hair cover, the cortex and central cylinder composed of parenchymal cells, cell secretion and the carrier files. The antioxidant activity of ethanol extract obtained from the calculation rhizome Consentrasion inhibition (IC50) ranged from 17.70 to 55.22 ppm. IC50 value of 17.70 ppm rhizome ethanol extract has antioxidant activity 5 times weaker compared to the control of vitamin C (IC50 3.71 ppm) and 3 times weaker than BHT (IC 50 5.57 ppm). At 55.22 ppm IC50 extract has antioxidant activity 15 times weaker compared to the control of vitamin C and 10 times weaker than the BHT. Secretory cell density relationship with the antioxidant activity in test with linear regression analysis showed that there was no relationship between the density of secretory cells per unit area with antioxidant activity in the rhizome of Curcuma xanthorrhiza.